2019
DOI: 10.1108/ijbm-10-2018-0272
|View full text |Cite
|
Sign up to set email alerts
|

The effects of risk appraisal and coping appraisal on the adoption intention of m-payment

Abstract: Purpose Although debit and credit cards are widely accepted, consumers still have significant concerns pertaining to the risk of the cards’ usage. Mobile payment (m-payment) acts as identification and a virtual card for consumers, and is viewed as more secure than card payments. However, the influence of consumers’ appraisal of debit and credit cards usage and using m-payment on the adoption intention of m-payment is unclear. Using the protection motivation theory, the purpose of this paper is to explore the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 57 publications
(82 reference statements)
1
10
1
Order By: Relevance
“…At the same time, self-efficacy had a lower impact on usage continuance intention. Consequently, the growth of self-efficiency would strengthen the intention to use cashless technologies, which is also in line with claims made by Wang (2020) in his research study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…At the same time, self-efficacy had a lower impact on usage continuance intention. Consequently, the growth of self-efficiency would strengthen the intention to use cashless technologies, which is also in line with claims made by Wang (2020) in his research study.…”
Section: Discussionsupporting
confidence: 87%
“…H4: Self-efficacy (SE) -There is a positive relationship between Self-efficacy and the adoption of cashless payment. SE had a positive and significant effect on trust in cashless technology, so increasing SE would directly increase the belief in cashless and online technology that is offered to customers, which is in harmony with claims made by Wang (2020)…”
Section: Resultsmentioning
confidence: 63%
“…There is consistent evidence that PMT is a robust model for explaining and promoting health and safety-related attitudes and behaviors (36,38), and "can be applied to any threat that an individual can assess and respond to accordingly" (55). In fact, it has been widely utilized in a diverse disciplines, such as medical care (36,58,59); environmental sciences (60)(61)(62); information security (63)(64)(65); and transportation (66)(67)(68). Recently, it has been observed that extensive epidemiological research employing PMT to study behavioral or psychological changes related to COVID-19 has been conducted.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/0265-2323.htm and contactless payment methods have been widely adopted in modern society and business, such as cheque, demand draft, debit/credit card, e-wallets, mobile wallets, net banking, near field communication-enabled mobile payment, quick response code and wearable (Apanasevic et al, 2016;Glavee-Geo et al, 2017;Karjaluoto et al, 2020;Liu et al, 2021;Loh et al, 2019;Patil et al, 2017;Verma et al, 2019;Wang, 2019;Zhao et al, 2019). Retailers have gradually implemented advanced cashless payment systems within their stores in the hope of reducing consumer waiting time, increasing transaction efficiency and enhancing consumer experience (Khalilzadeh et al, 2017;Leong et al, 2013;Thales Group, 2020).…”
mentioning
confidence: 99%